2021
DOI: 10.2306/scienceasia1513-1874.2021.007
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation structure of wetlands in Eastern Himalayan Highlands of Gasa, Bhutan

Abstract: The study was conducted on the unexplored wetland vegetation of the eastern Himalayan highlands of Gasa District, Northern Bhutan. A random quadrat sampling of 1 × 1 m 2 method was used to assess the presenceabsence of species, including shrubs, trees, mosses, ferns, and climbers, that were occurring adjacent to plots. Altogether, 201 taxa from 81 families, distributed in 149 genera, were recorded. Among the total species, 6 bryophytes, 20 monilophytes, 2 gymnosperms, and 173 angiosperms species were found. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In addition, higher SOC in forestland might be another reason. Previous studies showed that characteristics of plant community depend on landuse types [28] and significantly influence stability of soil aggregates via changing SOC and soil microbial biomass [29]. Zhao et al [10] reported that landuse types contributed to about 67% variation of soil aggregates, which implied that land use was a main factor influencing soil aggregate stability and size distribution.…”
Section: Land Use Impact On Soil Aggregatesmentioning
confidence: 99%
“…In addition, higher SOC in forestland might be another reason. Previous studies showed that characteristics of plant community depend on landuse types [28] and significantly influence stability of soil aggregates via changing SOC and soil microbial biomass [29]. Zhao et al [10] reported that landuse types contributed to about 67% variation of soil aggregates, which implied that land use was a main factor influencing soil aggregate stability and size distribution.…”
Section: Land Use Impact On Soil Aggregatesmentioning
confidence: 99%
“…Wetland is an important part of ecosystem, which has important ecological, economic and social value. However, many wetlands have suffered serious damage due to human activities (Tendar and Sridith, 2021). For the needs of human activities such as agriculture, urbanization and industrialization, many wetlands have been filled and reclaimed, leading to the disappearance and reduction of wetlands (Rashid et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The profile diagrams are crucial in describing certain general features of the forest structures that are not well represented and explained by the photographs and quantitative data [7]. Understanding plant diversity, composition, and structural profile is imperative for forest ecological study and provides essential information for long-term monitoring of environmental change, forest management, and wildlife conservation [4,6,8,9].…”
Section: Introductionmentioning
confidence: 99%